Investigation of some chemotherapy drugs induce cardiotoxicity - Asia A. Mahdi; Basma H. Bedair; Ashjan M. Hussein; Alyaa K. Abood; Rabiah M. Sabri; Shams A. Mohammed; Eman G. Metaab; Reem H. Al-Tabra; Nada H. Bedair; Moustafa A. Gouda; Asmaa A. Jawad; Abbas K. Abbas (Al-SalamJournal for Medical Science)
The risk of long-term cardiovascular problems resulting from cancer treatment is rising due to the growing population of cancer patients. Cancer therapy-induced cardiotoxicity (CTIC) is a partially elucidated consequence of diverse chemotherapeutic drugs, targeted anti-cancer treatments, and radiation treatment. It is usually identified clinically by a decrease in left ventricular ejection fraction, evaluated by echocardiography. Nonetheless, the emergence of cardiac functional decline signifies irreparable heart injury, underscoring the need for the development of diagnostics capable of identifying CTIC before the commencement of functional deterioration. Growing evidence indicates that abnormal changes in heart metabolism significantly contribute to the onset of CTIC. The treatment progress has significantly enhanced the recovery rate of cancer patients. This better longevity is concomitant with increased risks for cardiovascular complications. Chemotherapy-induced cardiotoxicity is a perilous outcome that limits the therapeutic use of various chemotherapy agents. This review analyses the prevalence of heart disease is caused by immunotherapeutic medicines and chemotherapy. The preventive characteristics of antioxidants and future possible concerns about cardiotoxicities caused by treatment are the primary topics of discussion in this study.